Evaluation of Methyl-3,4 Dihydroxybenzoate for Renal Protection in Rat Model of Streptozotocin–Nicotinamide-Induced Diabetic Nephropathy - Rakotonarivo, Heriniaina Luca; Kilari , Eswar Kumar; Harh , M. Abdullah; N M Manikumari, Kusumanchi (Journal of Neonatal Surgery, 2026)
Diabetic nephropathy (DN) is a serious microvascular impediment accompanying with type 2 diabetes that is characterized by progressive kidney damage resulting from increased oxidative stress and metabolic disruption. Many studies have described the antioxidant activity of phenols; as such, it can be speculated that these compounds may be used to treat some of the complications of diabetes. In this context, the current study investigated the nephroprotective efficacy of Methyl-3,4 Dihydroxybenzoate (MDHDB) against streptozotocin-nicotinamide-induced diabetic nephropathy (DN) in Wistar rats. DN was developed in Wistar rats using streptozotocin (40 mg/kg) given intraperitoneally 15 min after nicotinamide (100 mg/kg) administration. After confirming the presence of diabetes, the rats were divided into four groups: normal control, disease control, or two experimental groups receiving MDHDB at either 200 mg/kg or 400 mg/kg. Fasting blood glucose (FBG), body weight, food intake and water intake were assessed. In addition, The renal function test and the lipid profile were done. The status of oxidative stress markers were also carried out in the renal tissue. Finally, the the histopathology of the kidney was analyzed. MDHDB treatment lead to a reduction of fasting blood glucose (FBG) ,HbA1c and the symptoms of polydipsia and anorexia were enhanced in diabetic rats. Both of the doses of MDHDB exhibited a dose-dependent repair of the renal function indicators in diabetic rats, with the highest dose (400 mg/kg) exhibiting significant decreases in serum creatinine, blood urea nitrogen, and total proteins. Therefore, the results of this investigation indicate that MDHDB exhibit nephroprotective effects against DN through its multiple mechanisms including antihyperglycemic activity, improvement of oxidative stress indicators, improvement of lipid metabolism, and maintenance of the structure of the kidneys..